Pedagogy of care in intercultural approaches to languages education - Marshall, Kelle L.; Bokhorst-Heng, Wendy D. (Cahiers de l’ILOB / OLBI Journal)

(untitled) (Centre canadien d’études et de recherche en bilinguisme et aménagement linguistique (CCERBAL), 2025)
Disruptions caused by the COVID-19 pandemic revealed in new ways the vulnerabilities of students’ sense of self, especially in the contexts of intercultural orientations to language education where critical self-reflection can be disorienting for learners. We propose a pedagogy of care to manage such decentering, aiding the formation of caring communities of practice and development of student flourishing. Our data derives from a teacher education course on intercultural orientations to language education and mediation, taught virtually in 2020. We analysed email exchanges between the professor and students and transcribed Zoom class sessions to examine the instructor’s pedagogy based on Noddings’s ethics of care. We identify six components within the instructor’s pedagogy: relationship; motivational displacement; person in context; flexibility; engrossment; mentality of care. Students’ expressions of reciprocity suggest possibilities for their own adoption of care and flourishing. We propose that a caring and compassionate approach to pedagogy can be instrumental in mediating a space where students might develop not only intercultural competencies but also a positionality of care.